PERANAN RESILIENSI TERHADAP WORK-STUDY CONFLICT PADA MAHASISWA MAGANG MBKM DI JABODETABEK - Sarah Enzelika; Riana Sahrani (STKIP Subang, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) program provides students with the opportunity to gain work experience through internship programs. However, students’ simultaneous involvement in the workforce and their academic studies has the potential to create work-study conflict, a condition in which the demands of work and academic demands clash with one another. Resilience, defined as an individual’s ability to adapt and bounce back from stress, is hypothesized to play a crucial role in managing this conflict. This study aims to examine the role of resilience in mitigating work-study conflict among students currently participating in the MBKM internship program in the Jabodetabek region. The study employs a quantitative approach with a sample of 240 students aged 19–22 years. Data analysis employed simple linear regression to test the role of the resilience variable on work-study conflict. The resilience variable was measured using the Academic Resilience Scale (ARS-30) (Cassidy, 2016), and the work-study conflict variable was measured using the work-study conflict scale (Olson, 2020). The results indicate that resilience significantly influences work-study conflict F(1,238) = 1149, p = .000 < .05), with a coefficient of determination of R² = .325. This means that resilience explains 32.5% of the variance in work-study conflict among MBKM internship students. These findings indicate that students with higher levels of resilience tend to experience lower levels of work-study conflict.